2020
DOI: 10.1371/journal.pntd.0008867
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate-Aedes aegypti and Culex quinquefasciatus (Diptera)-arbovirus transmission networks: Non-human feeding revealed by meta-barcoding and next-generation sequencing

Abstract: Background Aedes aegypti mosquito-borne viruses including Zika (ZIKV), dengue (DENV), yellow fever (YFV), and chikungunya (CHIKV) have emerged and re-emerged globally, resulting in an elevated burden of human disease. Aedes aegypti is found worldwide in tropical, sub-tropical, and temperate areas. The characterization of mosquito blood meals is essential to understand the transmission dynamics of mosquito-vectored pathogens. Methodology/principal findings Here, we report Ae. aegypti and Culex quinquefasciatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 48 publications
1
27
1
Order By: Relevance
“…quinquefasciatus fed on a wide range of hosts such as cow, horse, chicken, human, turkey, greattailed grackle, Virginia opossum, and Muscovy duck, all species common in farmland settings. This result contrasts with other studies; Janssen et al (44) found humans were its primary host food (63-77%), whereas Estrada-Franco et al (56) found it fed largely on dogs. Interestingly, (89) found it used diverse hosts in Nevada, USA.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…quinquefasciatus fed on a wide range of hosts such as cow, horse, chicken, human, turkey, greattailed grackle, Virginia opossum, and Muscovy duck, all species common in farmland settings. This result contrasts with other studies; Janssen et al (44) found humans were its primary host food (63-77%), whereas Estrada-Franco et al (56) found it fed largely on dogs. Interestingly, (89) found it used diverse hosts in Nevada, USA.…”
Section: Discussioncontrasting
confidence: 63%
“…Our results suggest that Cx. quinquefasciatus is mainly ornithophilic across sylvan communities in Chiapas State, but also feeds on mammals, confirming that it could have an important bridge role in arbovirus transmission (3,42,56,(90)(91)(92)(93).…”
Section: Discussionmentioning
confidence: 94%
“…This approach may yield hundreds of thousands of sequence reads per individual vector, as opposed to the single sequence trace generated using the Sanger approach. The use of amplicon deep sequencing in arthropod vector bloodmeal analysis has afforded the detection of: up to four vertebrate hosts in some Rhodnius vectors 14 , different individual humans in Anopheles mosquitoes 7 , non-human feeding in Aedes aegypti and Culex quinquefasciatus 16 , and simultaneous identification of host, ectoparasite, and pathogen DNA in ticks and fleas 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Mosquitoes are the intermediate host of many viruses, playing an important part in the spread of numerous viral infectious diseases (Zhu et al, 2019;Estrada-Franco et al, 2020).…”
Section: Discussionmentioning
confidence: 99%